Advances in Stromatolite Geobiology - Reitner, Joachim; Quéric, Nadia-Valérie; Arp, Gernot (Lecture Notes in Earth Sciences, 2011)
Stromatolites are the most intriguing geobiological structures of the entire earth history since the beginning of the fossil record in the Archaean. Stromatolites and microbialites are interpreted as biosedimentological remains of biofilms and microbial mats. These structures are important environmental and evolutionary archives which give us information about ancient habitats, biodiversity, and evolution of complex benthic ecosystems. However, many geobiological aspects of these structures are still unknown or only poorly understood. The present proceedings highlight the new ideas and information on the formation and environmental setting of stromatolites presented at the occasion of the Kalkowsky Symposium 2008, held in Göttingen, Germany.